High-Level Production of Human Leptin by Fed-Batch Cultivation of Recombinant Escherichia coli and Its Purification - Jeong, Ki Jun (American Society for Microbiology, 1999)
Human leptin is a 16-kDa (146-amino-acid) protein that is secreted from adipocytes and influences body weight homeostasis. In order to obtain high-level production of leptin, the human obese gene coding for leptin was expressed in Escherichia coli BL21(DE3) under the strong inducible T7 promoter. The recombinant leptin was produced as inclusion bodies in E. coli, and the recombinant leptin content was as high as 54% of the total protein content. For production of recombinant human leptin in large amounts, pH-stat fed-batch cultures were grown. Expression of leptin was induced at three different cell optical densities at 600 nm (OD(600)), 30, 90, and 140. When cells were induced at an OD(600) of 90, the amount of leptin produced was 9.7 g/liter (37% of the total protein). After simple purification steps consisting of inclusion body isolation, denaturation and refolding, and anion-exchange chromatography, 144.9 mg of leptin that was more than 90% pure was obtained from a 50-ml culture, and the recovery yield was 41.1%.